Kinematic Analysis and Simulation of a Cross Axis of Single Spider Universal Joint - Fan Jingfeng; Li Dalei (Jixie chuandong)
The kinematic analysis of a single spider universal joint is carried out,by using mathematical vector method,the transfer movement relationship of a single spider universal joint and the cross axis plane normal trajectory equation are obtained. By using the Solid Works Motion software,the kinematic trajectory of a single spider universal joint cross axis is simulated,comparing the simulated wave chart with the calculated theoretical equation,the correctness of the theoretical analysis results is verified,a theoretical basis for the single spider universal joint movement optimized design is provided. At the same time in space,a theoretical reference for the spatial arrangement of single spider universal joint steering system is provided.